Human Endogenous Retrovirus-K and TDP-43 Expression Bridges ALS and HIV Neuropathology - Douville, Renée N.; Nath, Avindra (Frontiers in Microbiology, 2017)
Despite the repetitive association of endogenous retroviruses in human disease, the mechanisms behind their pathological contributions remain to be resolved. Here we discuss how neuronal human endogenous retrovirus-K (HERV-K) expression in Human Immunodeficiency virus (HIV)-infected individuals is a distinct pathological aspect of HIV-associated neurological conditions, such as HIV encephalitis and HIV-associated neurocognitive disorders. Enhanced neuronal HERV-K levels were observed in the majority of HIV-infected individuals, and to a higher degree in brain tissue marked by HIV replication. Moreover, we highlight an important neuropathological overlap between amyotrophic lateral sclerosis and HIV encephalitis, that being the formation of neurotoxic TDP-43 deposits in neurons. Herein, we argue for enhanced transdisciplinary research in the field of ERV biology, using an example of how HERV-K expression has novel mechanistic and therapeutic implications for HIV neuropathology.